Interannual changes of stratospheric temperature and ozone:Forcing by anomalous wave driving and the QBO - Salby, Murry L. (Journal of the Atmospheric Sciences, 2011)
A 3D model of dynamics and photochemistry is used to investigate interannual changes of stratospheric dynamical and chemical structure through their dependence on tropospheric planetary waves and on the quasi-biennial oscillation (QBO). The integrations reproduce the salient features of the climate sensitivities of temperature and ozone, which have been composited from the observed records of ECMWFand the Total Ozone Mapping Spectrometer (TOMS). Characterized by a strong anomaly of one sign at polar latitudes and a comparatively weak anomaly of opposite sign at subpolar latitudes, each bears the signature of the residual mean circulation. The structure is very similar to that associated with the Arctic Oscillation. The integrations imply that, jointly, anomalous Eliassen-Palm (EP) flux transmitted from the troposphere by planetary waves and the QBO are the major mechanisms behind interannual changes in the stratosphere. An analogous conclusion follows from the observational record. During early winter, anomalous temperature and ozone are accounted for almost entirely by anomalous EP flux from the troposphere, as they are in the observational record. During late winter, both mechanisms are required to reproduce observed anomalies. Although the QBO forces anomalous structure equatorward of 40°N, the strong anomaly over the Arctic follows principally from anomalous upward EP flux. Reflecting anomalous wave driving of residual mean motion, the change of EP flux leads to anomalous downwelling of ozone-rich air. In concert with isentropic mixing by planetary waves, the anomalous enrichment that ensues at extratropical latitudes sharply modifies total ozone over the Arctic. Integrations distinguished by the omission of heterogeneous processes indicate that chemical destruction accounts for approximately 20% of the anomaly in Arctic ozone between warm and cold winters. Analogous to estimates derived from the observed record of the Solar Backscatter Ultraviolet, version 8 (SBUV-V8) instrument, the remaining approximately ...